Is a third proton-conducting pathway operative in bacterial cytochrome c oxidase? - Salje, J; Ludwig, B; Richter, O (2005)
Despite the existence of several three-dimensional structures of cytochrome c oxidases, a detailed understanding of pathways involved in proton movements through the complex remains largely elusive. Next to the two well-established pathways (termed D and K), an additional proton-conducting network ('H-channel') has been proposed for the beef heart enzyme. Yet, our recent mutational studies on corresponding residues of the Paracoccus denitrificans cytochrome c oxidase provide no clues that such a pathway operates in the prokaryotic enzyme.